1985
DOI: 10.1002/jrs.1250160402
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra and structures of the high‐ and low‐temperature phases in the two‐dimensional layer‐type compound (CH3CH2NH3)2SnCl6

Abstract: Polarized Raman spectra of oriented single crystals of (CH,CH,NH,),SnCl, measured over the temperature range 15-300 K have been used to investigate the mechanism of the structural transition at 125 K. A detailed study of some of the external modes and of the internal modes of both the SnClk and CH3CH2NH: ions in the high-and low-temperature phases has enabled the structure of the disordered high-temperature phase to be confirmed and suggestions for the structure of the low-temperature phase to be proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The understanding of phase transitions of these hybrid structures is quite important from materials point of view. In addition, these compounds exhibit numerous structural phase transitions related to reorientation motion in the organic part, [3][4][5][6][7] and so are classified to be of "order-disorder". Raman scattering investigations as a function of temperature present great interest since this indirectly brings information regarding molecular conformation and how the cations contribute to the mechanism of the phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of phase transitions of these hybrid structures is quite important from materials point of view. In addition, these compounds exhibit numerous structural phase transitions related to reorientation motion in the organic part, [3][4][5][6][7] and so are classified to be of "order-disorder". Raman scattering investigations as a function of temperature present great interest since this indirectly brings information regarding molecular conformation and how the cations contribute to the mechanism of the phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…in the kHz range [21], the highfrequency critical fluctuation observed in the 200 MHz NMR spin-lattice relaxation is believed to be the collective flip-flops of the NH 3 polar head. Because the NH 3 polar head is known to spend its time between two favorable sites in the disordered phase [3,28,29], we have employed the kinetic Ising model in order to check the conjecture, satisfactorily describing the experimental results [4,27].…”
Section: Resultsmentioning
confidence: 98%
“…In our previous 1 H NMR studies of the CnSn systems, two typical successive phase transitions were observed [4][5][6][7]: (a) order-disorder transition of the rigid alkyl chains accompanied by a uniaxial reorientation about their long axes along with the flipping of the polar groups, such as NH 3 , between the potential wells, and (b) conformational transition leading to a partial melting of the alkyl chain part. In the low temperature (LT) phase below the order-disorder transition temperature, the alkyl chains are rigid and adopt an all-trans conformation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations